2017
DOI: 10.1016/j.jtos.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Human Tear Fluid Reduces Culturability of Contact Lens-Associated Pseudomonas aeruginosa Biofilms but Induces Expression of the Virulence-Associated Type III Secretion System

Abstract: Purpose The type III secretion system (T3SS) is a significant virulence determinant for Pseudomonas aeruginosa. Using a rodent model, we found that contact lens (CL)-related corneal infections were associated with lens surface biofilms. Here, we studied the impact of human tear fluid on CL-associated biofilm growth and T3SS expression. Methods P. aeruginosa biofilms were formed on contact lenses for up to 7 days with or without human tear fluid, then exposed to tear fluid for 5 or 24 h. Biofilms were imaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Non-bacteriostatic activities of tear fluid also include its capacity to disperse P . aeruginosa biofilms [ 16 ], which are thought to be key to the pathogenesis of device-related infections.…”
Section: Introductionmentioning
confidence: 99%
“…Non-bacteriostatic activities of tear fluid also include its capacity to disperse P . aeruginosa biofilms [ 16 ], which are thought to be key to the pathogenesis of device-related infections.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between experimental and physiological conditions should be also considered for interpretation of our results. The dynamic tear clearance and lens movement were absent in our experimental settings and these two factors might change the biofilm kinetics in human ocular surface [ 46 ]. Finally, the effect of NO on multispecies biofilms was not investigated even though multispecies-associated keratitis is common with contact lens wear [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested the presence of bacterial biofilms on the infected ocular surface and have demonstrated an enhanced biofilm formation capability of ocular bacterial clinical isolates in vitro ( 7 11 ). Microscopic inspections have demonstrated the presence of bacterial aggregates and biofilm matrix in experimental infections of the mouse cornea ( 12 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has been presented that the P. aeruginosa type III secretion system (T3SS) contributes to the pathogenesis of P. aeruginosa keratitis. Thus, the T3SS activity of P. aeruginosa was shown to prevent reactive oxygen species (reactive oxygen species) production by neutrophils as well as to cause neutrophil apoptosis during corneal infection ( 11 , 17 19 ). However, previous in vitro studies have demonstrated an inverse correlation between the expression of biofilm factors and T3SS in P. aeruginosa ( 20 , 21 ), and more evidence is needed for a role of both biofilm formation and T3SS in corneal infection.…”
Section: Introductionmentioning
confidence: 99%